Excess liver‐related mortality among people with AIDS compared to the general population: an Italian nationwide cohort study using multiple causes of death. Issue 10 (2nd September 2020) - Taborelli, M; Suligoi, B; Toffolutti, F; Frova, L; Grande, E; Grippo, F; Pappagallo, M; Pugliese, L; Regine, V; Serraino, D; Zucchetto, A
Abstract : Objectives: Liver diseases have become a leading cause of death among people with AIDS (PWA). This study aimed to investigate whether PWA experienced excess mortality related to liver diseases as compared to the general population (non‐PWA), using a multiple cause of death (MCoD; i.e. all conditions reported on death certificates) approach. Methods: A population‐based, nationwide, retrospective cohort study was conducted among Italian people, aged 15–74 years, who had been diagnosed with AIDS since 2006. Date of death and MCoD data were retrieved, up to December 2015, by individual record linkage with national mortality data. Sex‐ and age‐standardized mortality ratios (SMRs), with 95% confidence intervals (CIs), were estimated by dividing the observed number of deaths related to a specific condition among PWA to the expected number, based on non‐PWA mortality rates. Results: Among 7912 PWA (34 184 person‐years), 2076 deaths occurred. The number of death certificates reporting liver diseases among MCoDs was 583 (28.1%), including 382 (18.4%) reporting viral hepatitis, 370 (17.8%) reporting nonviral liver diseases, and 41 (2.0%) reporting liver cancers. The corresponding SMRs were 40.4 (95% CI 37.2–43.8) for all liver diseases, 131.1 (95% CI 118.3–145.0) for viral hepatitis, 29.9 (95% CI 27.0–33.1) for nonviral liver diseases, and 11.2 (95% CI 8.1–15.3) for liver cancers. Particularly elevated SMRs emerged among PWA aged 15–49 years and those infected by injecting drug use. Conclusions: The high excess liver‐related mortality observed among PWA warrants preventive actions to limit the burden of viral hepatitis coinfections, alcohol abuse, and metabolic disorders, especially among younger PWA and injecting drug users.